Program PendampinganMahasiswa Pada PembuatanNaskah Tutorial Media Pembelajaran Matematika Berbasis Aplikasi - tb sofwan; Rina Oktaviyanthi (Jejaring Penelitian dan Pengabdian Masyarakat, 2023)
The use of mathematics learning media based on applications and online platforms has grown rapidly during the Covid-19 pandemic. Three years have passed, and the post-Covid-19 pandemic learning trend is conducted through blended learning or hybrid learning. Referring to this condition, both educators and prospective educators, including mathematics educators, need to respond to the needs of using mathematics learning media involving technology by preparing the best possible supporting tools such as teaching modules and application usage tutorials. In practice, the compilation of these tutorial scripts has been widely done, but those that adapt the content and objectives of mathematics learning in junior high schools and high schools made by prospective mathematics teachers is still very limited. Therefore, it is necessary to provide guidance to prospective mathematics teacher students in creating tutorial scripts for mathematics learning media based on applications. This guidance activity is carried out using the Participatory Learning and Action (PLA) method, which is divided into three stages: (1) the initial stage where the executing team formulates the activity scenario and presentation materials as well as examples of simulations to be delivered, (2) the core stage where the delivery of theory and practice activities is carried out, and (3) the final stage where the executing team evaluates the guidance activities, including assessing the participants' performance and their responses to the activities. In general, the success target of the guidance is achieved on average above 50%. A total of 11 out of 21 participants in the guidance, or 52%, fulfilled both completion indicators of the guidance, namely creating tutorial scripts and presentation videos.